Beyond the notes : teaching and learning music at Historically Black Colleges and Universities - Grissom-Broughton, Paula A. (Emerald Publishing Limited, 2025)
Beyond the Notes: Teaching and Learning Music at Historically Black Colleges and Universities examines teaching and learning music at America's Historically Black Colleges and Universities (HBCUs) through a quadripartite framework - the context (sociocultural influences and institutional missions); the constituents (demographic and characteristics traits of students, faculty, and surrounding communities); the construct (curricula design and instructional delivery); and the confluence (an explanation of why the context, constituents, and construct all must be considered simultaneously). The book is divided into four sections based on the thematic perspectives from the C4 quadripartite framework. The first section provides historical information pertinent to why specific institutions were founded for African Americans. The second section examines the unique positioning of African Americans in the narratives of higher education and the implications of their omission from the historical literature for music education practices. The third section explores the music curricula and specific pedagogical approaches for teaching at HBCUs and considers various ways the music classroom can serve to deconstruct the systems of ideology that have historically marginalized, suppressed, and subjugated minoritized voices within the field of music. The fourth and final section posits the importance of simultaneously considering the aforementioned thematic perspectives in order to address institutional systems that perpetuate discrimination within music classrooms. Beyond the Notes is valuable reading for students and Faculty at HBCUs, Higher Education administrators, and anyone with a passion for music education and a desire to understand the unique challenges and opportunities within HBCUs.